La educación en tiempos de confinamiento Perspectivas de lo pedagógico - Romero - Solange Tenorio, Marcela (Ariadna Ediciones, 2021)
This book presents a set of essays that discuss various central aspects of the relationship between pandemic and education, beginning with a macro view, examining the political dimension and education. From reading this book we gather an exhaustive knowledge. It is remarkable that from the Faculty of Philosophy and Education of the UMCE, contributions on a new and fluid topic such as the pandemic have been compiled in a short time. Taken together, the essays in this book are a robust and powerful example of how scientific knowledge is constructed.